Evaluation Of Several Brands And Frying Cycles On The Characteristics Of Used Cooking Oil - Firdaus, Salsabila; Yulistiani, Ratna (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Repeated use of cooking oil alters its physical and chemical structure and the quality of fried foods. This study aimed to evaluate the quality of used cooking oil across brands and frying cycles, in accordance with SNI 7709:2019. The research used a Completely Randomized Design (CRD) in a factorial pattern with two factors and three replications. Factor I: cooking oil brands (Sunco, Minyak Kita, Bulk). Factor II: number of frying cycles (4 and 5 cycles). Data were analysed using ANOVA, the 5% DMRT post hoc test, and the Friedman test for sensory evaluation. The results showed that used cooking oil of the Sunco brand with 4 and 5 frying cycles still met SNI 7709:2019 standards, with physicochemical characteristics of color, aroma, and clarity preferred by panelists; water content (0.10% and 0.10%); free fatty acid content (0.17% and 0.26%); peroxide value (0.47 meq O?/kg and 0.47 meq O?/kg); and smoke point (238.88°C and 235.44°C). Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 12: Responsible Consumption and Production